2021
DOI: 10.1186/s12935-021-01867-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a tumor microenvironment-related gene signature to improve the prediction of cervical cancer prognosis

Abstract: Background Previous studies have found that the microenvironment of cervical cancer (CESC) affects the progression and treatment of this disease. Thus, we constructed a multigene model to assess the survival of patients with cervical cancer. Methods We scored 307 CESC samples from The Cancer Genome Atlas (TCGA) and divided them into high and low matrix and immune scores using the ESTIMATE algorithm for differential gene analysis. Cervical cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In this study, we attempted to establish a predictive model with four immune-related genes with an expression matrix of 1-or-2 to replace their previous specific expression values. To a certain extent, we avoided the problem caused by platform differences and detecting technique to a certain extent, so as to make up for the limitations of previous studies (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we attempted to establish a predictive model with four immune-related genes with an expression matrix of 1-or-2 to replace their previous specific expression values. To a certain extent, we avoided the problem caused by platform differences and detecting technique to a certain extent, so as to make up for the limitations of previous studies (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of their model with immune infiltration was not definitely pinpointed and had nothing to do with clinicopathological characteristics. In four latest published studies, researchers have reclassified the cervical cancer cohorts and established gene signature derived from the ESTIMATE algorithm or constructed specific TMEscore based on the penetration pattern of immune cells to evaluate the relationship between immune infiltration and prognosis (20)(21)(22)(23). Considering the relatively great differences between tumor and normal tissues, we aimed at exploring the heterogeneity in immune landscape of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, taken together, we believe that this model can be used to evaluate the prognostic risk in cervical cancer patients. And our model is better than other cervical cancer models [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 85%
“…SLAMF1 (CD150) and SLAMF6 belong to the signaling lymphocytic activation molecule (SLAM) family and express on several immune cells including T cells, B cells, and NK cells ( 56 ). Previous studies have shown that the expressions of SLAMF1 in cervical cancer and SLAMF6 in liver cancer were closely related to tumor infiltration of immune cells and patient prognosis ( 57 , 58 ). The SH2D1A gene encodes SH2 domain-containing protein 1A, which is often known as SLAM-associated protein.…”
Section: Discussionmentioning
confidence: 99%